Age‐Related Cortical Thickness Reduction in Non‐Demented Down's Syndrome Subjects. Issue 1 (21st May 2015) - Romano, Andrea; Cornia, Riccardo; Moraschi, Marta; Bozzao, Alessandro; Chiacchiararelli, Laura; Coppola, Valeria; Iani, Cristina; Stella, Giacomo; Albertini, Giorgio; Pierallini, Alberto
ABSTRACT: BACKGROUND AND PURPOSE: The aim of this study was to investigate the characteristic pattern of age‐related cortical thinning in patients with Down Syndrome (DS), as assessed by MRI and automatic cortical thickness measurements. METHODS: Ninety‐one non‐demented subjects with DS (range 11–53 years) were examined using a 1.5 T scanner. MRI‐based quantification of cortical thickness was performed using FreeSurfer software package., The Pearson product‐moment correlation coefficient between age and mean cortical thickness was evaluated for all subjects participating in the study. RESULTS: A significant negative correlation between cortical thickness and age was found bilaterally in the frontal, temporal, parietal and cingulate gyrus. Specific investigation of cerebral lobes showed a more evident involvement of the frontal one, compared to others. Moreover, the age related reduction of cortical thickness appeared to be more significant and rapid in patients between 20 and 30 years of age. CONCLUSIONS: Our findings showed that Down Syndrome subjects are affected by a diffuse cortical thinning. The involvement of cortical structures can be observed at an earlier age than previous studies have reported.